2016
DOI: 10.1111/cdev.12598
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Dynamics of Intergroup Contact and Intergroup Attitudes: Long‐Term Effects in Adolescence and Early Adulthood

Abstract: Intergroup contact represents a powerful way to improve intergroup attitudes and to overcome prejudice and discrimination. However, long-term effects of intergroup contact that consider social network dynamics have rarely been studied at a young age. Study 1 validated an optimized social network approach to investigate intergroup contact (N = 6,457; Mage  = 14.91 years). Study 2 explored the developmental trajectories of intergroup contact by applying this validated network approach in a cross-sequential desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(167 citation statements)
references
References 50 publications
9
158
0
Order By: Relevance
“…In particular, students’ ICA tended to remain or become more like those of their friends over time (influence effect). Although past research has found that peers influence one another's public regard (Santos et al., ) and that intergroup contact influences intergroup attitudes over time (Wölfer, Schmid, Hewstone, & van Zalk, ), the results for ICA are new and represent an extremely important finding.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, students’ ICA tended to remain or become more like those of their friends over time (influence effect). Although past research has found that peers influence one another's public regard (Santos et al., ) and that intergroup contact influences intergroup attitudes over time (Wölfer, Schmid, Hewstone, & van Zalk, ), the results for ICA are new and represent an extremely important finding.…”
Section: Discussionmentioning
confidence: 95%
“…We then averaged the ingroup friends’ self‐reported outgroup contact. We followed this procedure using data collected as part of the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU) project (Wölfer, Schmid, Hewstone, & van Zalk, under review). We then conducted multilevel analyses (within‐level: students, between‐level: classes), separately for majority and minority students, in order to predict outgroup attitudes, while controlling for the ethnic density of the school, direct contact, number of ingroup friends, density, and reciprocity in network data.…”
Section: The Diversity Debate and The Missing Role Of Contactmentioning
confidence: 99%
“…Its suggested constructs are particularly relevant in adolescence due to fundamental cognitive and psychosocial changes that occur during this period and affect the development of attitudes and subjective norms. In line with the impressionable years hypothesis (Krosnick & Alwin, 1989), the literature repeatedly demonstrates that attitudes are formed during a period of mental plasticity in adolescence, before they tend to crystallize in adulthood and remain relatively stable afterward (e.g., W€ olfer, Schmid, Hewstone, & van Zalk, 2016). Moreover, adolescence is well known for the increasing impact of peers on adolescents' social development (Brechwald & Prinstein, 2011;LaFontana & Cillessen, 2010), whose influence, in turn, increases the salience of social norms.…”
Section: Developing Suitable Preventive Models For Cyberbullyingmentioning
confidence: 88%